Architectures of Inequality: Gender Pay Inequity and Britain's Finance Sector - Rachel Verdin (Bristol University Press, 2024)
The gender pay gap is economically irrational and yet stubbornly persistent. Focusing on the UK finance industry which is known for its gender pay disparity, this book explores the initiatives to fix gendered inequities in the workplace. Rachel Verdin crafts a unique framework, weaving extensive organizational data with women's lived experiences. Interviews uncover gaps in pay transparency, obstacles hindering workplace policies and the factors that are stalling progress for the future. This is an invaluable resource that offers key insights into gender equality and EDI measures shaped by legal regulations as well as corporate-driven initiatives.
Keywords: 320; Banking and finance; Equality; diversity and inclusion; Gender pay gap; Pay transparency; Work and employment